Radiation-induced moution of liquid inclusions in alkali halide crystals - Kulik, A.P.; Podshyvalova, O.V.; Marchenko, I.G. (Вопросы атомной науки и техники, 2019)
The radiation-stimulated behavior of liquid inclusions in KCl crystal was studied. It was shown that due to irradiation the inclusions become movable. It can result in the migration of such objects to the boundary of the material and the release of radioactive elements from the disposal. The trajectories of spontaneously migrating inclusions of various sizes were investigated in crystals irradiated by electrons and γ-quanta. Вивчено радіаційно-стимульовану поведінку рідких включень у монокристалах KCl. Показано, що під дією опромінення включення стають рухливими. Це може призводити до міграції таких об'єктів на межу матеріалу і виходу радіоактивних елементів із поховання. Досліджено траєкторії самочинної міграції включень різних розмірів у кристалах, опромінених електронами і γ-квантами. Изучено радиационно-стимулированное поведение жидких включений в монокристаллах KCl. Показано, что под действием облучения включения становятся подвижными. Это может приводить к миграции таких объектов на границу материала и выходу радиоактивных элементов из захоронения. Исследованы траектории самопроизвольной миграции включений различных размеров в кристаллах, облученных электронами и γ-квантами.